Identification of photoperiod-induced specific miRNAs in the adrenal glands of Sunite sheep (Ovis aries) - Du, Xiaolong; He, Xiaoyun; Liu, Qingqing; Liu, Qiuyue; Di, Ran; Chu, Mingxing (Frontiers in Veterinary Science, 2022)
In seasonal estrus, it is well known that melatonin-regulated biorhythm plays a key role. Some studies indicate that the adrenal gland plays an important role in reproduction in mammals, but the molecular mechanism is not clear. This study used an artificially controlled light photoperiod model, combined with RNA-seq technology and bioinformatics analysis, to analyze the messenger RNA (mRNA) and microRNA (miRNA) of ewe (Sunite) adrenal glands under different photoperiod treatments. After identification, the key candidate genes GRHL2, CENPF, FGF16 and SLC25A30 that photoperiod affects reproduction were confirmed. The miRNAs (oar-miR-544-3p, oar-miR-411b-5p, oar-miR-376e-3p, oar-miR-376d, oar-miR-376b-3p, oar-miR-376a-3p) were specifically expressed in the adrenal gland. The candidate mRNA-miRNA pairs (e.g., SLC25A30 coagulated by novel miRNA554, novel miRNA555 and novel miRNA559) may affect seasonal estrus. In summary, we constructed relation network of the mRNAs and miRNAs of sheep adrenal glands using RNA sequencing and bioinformatics analysis, thereby, providing a valuable genetic variation resource for sheep genome research, which will contribute to the study of complex traits in sheep.